The archaeology of Midas and the Phrygians: recent work at Gordion - Kealhofer, Lisa (University of Pennsylvania Museum of Archaeology and Anthropology, 2005)
Cover -- Title -- Copyright -- Contents -- 1 Recent Work at Gordion -- I: EXCAVATIONS, HISTORY, AND DATING AT GORDION -- 2 Gordion: Exploration over a Century -- 3 Old Problems and New Solutions: Recent Excavations at Gordion -- 4 Greek Pottery and Gordion Chronology -- 5 Reconstructing the Roman-period Town at Gordion -- II: INTERPRETING THE FINDS FROM GORDION -- 6 Textile Production at Gordion and the Phrygian Economy -- 7 A Decorated Roof at Gordion: What Tiles Are Revealing about the Phrygian Past -- 8 Glass Vessels from Gordion: Trade and Influence Along the Royal Road -- 9 A Preliminary Report on the Human Skeletal Material from Gordion's Lower Town Area -- 10 The Local Potter's Craft at Phrygian Gordion -- III: GORDION IN ITS REGIONAL CONTEXT -- 11 Settlement and Land Use: The Gordion Regional Survey -- 12 Ceramic Compositional Analysis and the Phrygian Sanctuary at Dümrek -- 13 Physical Geography, Land Use, and Human Impact at Gordion -- 14 Ethnographic Lessons for Past Agro-Pastoral Systems in the Sakarya-Porsuk Valleys -- IV: CONSERVING GORDION AND ITS ARTIFACTS -- 15 Support and Conserve: Conservation and Environmental Monitoring of the Tomb Chamber of Tumulus MM -- 16 Recent Conservation Research: Soluble Salts in Gordion Ceramics -- 17 Architectural Conservation at Gordion -- Bibliography -- Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- X -- Y -- Z -- Color Plate.